A caecal pseoudotumour with an incidental adenomatoid testicular tumour in a man with right undescended testis: a case report. Issue 1 (December 2016) - Muturi, Alex; Kotecha, Vihar; Ojee, Cynthia; Mang'oka, Desmond; Muthuri, John
Abstract Background Inflammatory pseudotumour refers to a non-malignant tumour-like mass resulting from an inflammatory reaction that is composed of granulation tissue with leukocyte infiltration that commonly occurs in the paediatric or young adult population. These tumours occur more commonly in the lungs and the orbit but rarely does it affect the gastrointestinal tract. It poses a clinical diagnostic challenge since it is a benign condition than can mimic the malignant counterpart. Our case is a rare presentation of the caecal pseudotumour in the presence of a right undescended abdominal testis evaluated as a caecal tumour with a differential diagnosis of a testicular malignancy. Case presentation We report a 53-year-old male who presented with clinical signs suggestive of right colon tumour and undescended right testis. Intra-operatively, a caecal mass was found with no clearly discernable appendix and extensive adhesion of the right colon to the retroperitoneum, to the liver and gall bladder. A testis was found adherent to the posterior aspect of the caecum and terminal ileum. A right hemicolectomy was performed. Histopathology findings revealed an inflammatory mass with abundant fibroblast proliferation and chronic inflammatory cells infiltrate, involving bowel wall and periceacal adipose tissue; no malignant cells were identified. The testis had within it an adenomatoid tumour nodule. He had uneventful recovery and was discharged home 7 days post-operatively. At the moment, he is symptoms free. Conclusions The occurrence of right colonic inflammatory pseudotumour and co-existent adenomatoid testicular tumour arising from a cryptorchid testis is very unusual. This would make one incline towards a malignant testicular lesion in the presence of cryptorchidism. Testicular adenomatoid tumour is a rare benign neoplasm, mostly affecting fully descended testis and usually does not warrant orchidectomy for purposes of preserving testicular function. On the other hand, surgical resection remains the only safe and curative treatment option available for inflammatory pseudotumours.